Sugarcane Fields: Harvest Systems and Residue Management - La Scala, Newton [UNESP]; Bordonal, Ricardo de Oliveira [UNESP]; Figueiredo, Eduardo Barretto de [UNESP]; Panosso, Alan Rodrigo [UNESP]; Moitinho, Mara Regina [UNESP]; Corradi, Mariana Marotti [UNESP]; Lal, R. (Crc Press-taylor & Francis Group, 2017)
Sugarcane (Saccharum officinarum) fields in Southern Brazil have been progressively converted from a burned harvest regime (BH) to a non-burned green mechanized harvest (GH), after which a large amount of crop residue is left on the soil surface. This conversion has resulted in ongoing social, economic, and environmental changes. In this entry, we analyze the aspects of soil physics and chemistry related to this conversion, with special emphasis on carbon dioxide (CO2) emissions and soil carbon (C) accumulation. We show how small changes in soil C stocks, related to increased soil CO2 emissions arising from different management options, can impact the C footprint of ethanol. Ethanol is an important option as a replacement for fossil fuels. The results we present and the mechanisms we discuss reveal an optimum land management strategy once the sugarcane areas are converted from a BH to a GH system, and the soil is left covered with sugarcane crop residue. Very different from a bare soil surface scenario, we predict that this is a more appropriate method for sustainable and long-term needs. Here, we maintain that when assessing the long-term effect of sugarcane-based ethanol production, consideration should be given to the long-term effects on the agroecosystem, particularly the soil being the basis for sustainability.